Livewriting the past, sceneliving the present: the historiography about the marginal culture in Piauí (Tempo e Argumento, 2013)
This paper attempts to cast reflections on the construction of a history about the culture and art in the marginal Piauí. In this analysis, discuss the ways in which such productions are shown inside and outside the academic environment in which gain greater visibility, in view of the formatting groups and research projects devoted to its study. It also intends to examine how the writing on the subject of Piauí historiography relates to that produced nationally, noting in particular the inclusion of local authors in collective publications with wider coverage.
Keywords: historiography; marginal culture; Piauí